Graphene oxide–upconversion nanoparticle based portable sensors for assessing nutritional deficiencies in crops - Giust, D; Lucío, M; El-Sagheer, A; Brown, T; Williams, L; Muskens, O; Kanaras, A (American Chemical Society, 2018)
The development of innovative technologies to rapidly detect biomarkers associated with nutritional deficiencies in crops is highly relevant to agriculture and thus could impact the future of food security. Zinc (Zn) is an important micronutrient in plants, and deficiency leads to poor health, quality, and yield of crops. We have developed portable sensors, based on graphene oxide and upconversion nanoparticles, which could be used in the early detection of Zn deficiency in crops, sensing mRNAs encoding members of the ZIP-transporter family in crops. ZIPs are membrane transport proteins, some of which are up-regulated at the early stages of Zn deficiency, and they are part of the biological mechanism by which crops respond to nutritional deficiency. The principle of these sensors is based on the intensity of the optical output resulting from the interaction of oligonucleotide-coated upconversion nanoparticles and graphene oxide in the absence or presence of a specific oligonucleotide target. The sensors can reliably detect mRNAs in RNA extracts from plants using a smartphone camera. Our work introduces the development of accurate and highly sensitive sensors for use in the field to determine crop nutrient status and ultimately facilitate economically important nutrient management decisions.